On the Semantics of Selfies (SoS) - Schneider, Tobias Matthias; Carbon, Claus-Christian (Frontiers in Communication, 2023)
Selfies are taken to communicate about mental conditions, aims, loves, and commitments. Until now, we lack a unified nomenclature or established classification system for selfies. We can retrieve information about the different types of selfies from various indicators. Most commonly, this is done by analyzing metatags, hashtags, or the linked message of the respective post. Alternatively, we can categorize the depicted selfie's subject or analyze how viewers describe the impression a selfie has on them. We refer to this latter approach as Semantics of Selfies (SoS). In the present study, participants (N = 132) were asked to generate spontaneous associations of selfies from a pool of 1,001 selfies in total. Cluster analyses revealed five main categories (Aesthetics, Imagination, Trait, State, and Theory of Mind) constituting a characteristic semantic profile for selfies. Consequently, the present article provides an understanding of how certain selfies affect viewers to perceive specific qualities in the self-portrayed person in a very compact visual form.